Use of cpSSRs for the characterisation of yam phylogeny in Benin - (:unkn) unknown (My University, 2005)
The Dioscorea cayenensis - Dioscorea rotundata species complex is the most widely cultivated yam in West Africa. This species complex has been described as deriving from wild yams belonging to the Enanthiophyllum section through domestication by African farmers. To study patterns of yam evolution and to establish phylogenetic relationships existing between wild and cultivated species sampled in Benin, we investigated changes in chloroplast DNA simple sequence repeats (cpSSR) in 148 yam accessions selected to cover the wider possible genetic diversity existing in the country. Dioscorea cayenensis and D. rotundata share the same haplotype. The morphotype "abyssinica" appeared to be subdivided into 2 haplotypes. One of these haplotypes shares the same haplotype with the Dioscorea cayenensis - Dioscorea rotundata species complex and with morphotypes praehensilis, suggesting that they might belong to the same species. Relationships among sections Lasiophyton, Macrocapaea, Opsophyton, and Enanthiophyllum were clarified, and some taxonomic changes within the Enanthiophyllum section were suggested. Dioscorea minutiflora, D. smilacifolia, and D. burkilliana might be considered as 1 single genetic group, and they are suspected of belonging to the same species
Keywords: African Research